Association Between Prosthetic Knee Effusions and Phosphodiesterase Type-5 Enzyme Inhibitor Use After Total Knee Arthroplasty: A Case Report. Issue 1 (10th January 2023) - Anibas, Jakob J.; Brady, Nicholas; Cheppalli, Naga Suresh
Abstract : Case: Phosphodiesterase type-5 enzyme (PDE5) inhibitors are well tolerated and used to treat erectile dysfunction. We report a case of prosthetic knee effusions associated with PDE5 inhibitor use in a 65-year-old man after total knee arthroplasty (TKA). PDE5 inhibitor treatment was stopped, and the patient had no further episodes of painful effusions. Conclusion: This report describes a previously unknown adverse effect of PDE5 inhibitor use in a prosthetic joint after TKA. We hope to encourage physicians managing patients after joint replacement to be aware of the association between PDE5 inhibitor use and recurrent joint effusions to improve postoperative outcomes.